1999
DOI: 10.1161/01.cir.99.13.1666
|View full text |Cite|
|
Sign up to set email alerts
|

Acute Anti-Ischemic Effect of Testosterone in Men With Coronary Artery Disease

Abstract: Short-term administration of testosterone induces a beneficial effect on exercise-induced myocardial ischemia in men with coronary artery disease. This effect may be related to a direct coronary-relaxing effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
181
0
4

Year Published

2000
2000
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(197 citation statements)
references
References 15 publications
10
181
0
4
Order By: Relevance
“…Indeed, testosterone infusion into the coronary arteries induces vasodilation, 76 and intravenous administration of testosterone reduces the exercise-induced ischemic response in men with stable angina. 77,78 Furthermore, acute administration of testosterone in men with chronic heart failure reduces peripheral vascular resistance and cardiac afterload, resulting in an increased cardiac index. 79 Chronic administration of testosterone also improves functional capacity and symptoms in heart failure patients.…”
Section: Clinical Effects Of Androgen Replacement Therapymentioning
confidence: 99%
“…Indeed, testosterone infusion into the coronary arteries induces vasodilation, 76 and intravenous administration of testosterone reduces the exercise-induced ischemic response in men with stable angina. 77,78 Furthermore, acute administration of testosterone in men with chronic heart failure reduces peripheral vascular resistance and cardiac afterload, resulting in an increased cardiac index. 79 Chronic administration of testosterone also improves functional capacity and symptoms in heart failure patients.…”
Section: Clinical Effects Of Androgen Replacement Therapymentioning
confidence: 99%
“…22,28 The lower testosterone and higher prolactin levels in females are in accordance with vasoconstriction and therefore with increased DBP reactivity and TPR reactivity. 40 This may interfere with blood pressure, and these parameters are therefore associated with the high rate of hypertension in stratum 3 subjects.…”
Section: Malesmentioning
confidence: 99%
“…32,[36][37][38] It is also reported that the vasorelaxing effect of testosterone is endothelium independent, with the possible involvement of potassium channel modulation. 39,40 There is a pressing need for epidemiological studies in Africa, to determine the risk factors for the development of hypertension in specific living circumstances. 41 This part of the transition and health during urbanization in South Africans (THU-SA) study was designed to determine the changes in the cardiovascular and endocrine parameters that may be associated with the high incidence of cardio/cerebrovascular disease in subjects living in informal settlements, compared with the rural community.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies support direct anti-anginal properties of T. T infusion has been related to coronary artery dilation and increased coronary blood flow, probably through inhibition of Ltype Ca2 + channels [110,111]. Intravenous T administration 30 min before exercise as well as 2 weeks of T treatment by transdermal patch had a positive effect on exercise induced ischemia [112,113]. Low T levels have been described in patients with heart failure.…”
Section: Cardiovascular Diseasementioning
confidence: 93%